The potential impact of environmental goods trade liberalization on trade and emissions - Marc Bacchetta; Eddy Bekkers; Jean-Marc Solleder; Enxhi Tresa (World Trade Organization (WTO), 2023)
We combine econometric estimation with quantitative modelling to generate projections on the trade, GDP, and emissions effects of a potential trade liberalization agreement in energy related environmental goods (EREGs) and environmentally preferable products (EPPs). Trade liberalization can contribute to reduced emissions in two ways in our projections: (i) a reduction of import prices of goods promoting energy efficiency; (ii) a reduction in the costs of intermediate and capital goods used in the production of electricity from renewable sources. We evaluate four scenarios combining reductions in tariffs and non-tariff measures (NTMs) of EREGs and EPPs. Using simulations with the WTO Global Trade Model findings show (i) an increase in exports of EREGs and EPPs both at the global level and in most regions; (ii) a modest increase in GDP in all regions because of falling tariffs, NTMs, and increased energy efficiency; (iii) a modest reduction in global emissions of about 0.6%. The dominant channel is energy efficiency whereas the costs of EREGs as intermediates in renewable energy production play a minor role, with or without end use control.
Keywords: F14; F13; F17; F18; Q56; 330; Environmental Goods (EGs); Trade Liberalization; Emissions; Energy efficiency